Effects of dimethyl ether on n-butane oxidation - Bekat, Tugce; Inal, Fikret (ELSEVIER SCI LTD, 2014)
Dimethyl ether (DME) is the simplest ether and it is used as an alternative fuel or fuel additive to reduce toxic emissions from combustion processes. The effects of DME on n-butane oxidation were investigated for two different concentrations of DME in the fuel mixture (i.e., 20% and 50%) and two different fuel-rich equivalence ratios (i.e., 2.6 and 3.0) using detailed chemical kinetic modeling. Reactor model was selected as atmospheric-pressure, adiabatic, tubular reactor, operated under laminar flow conditions. The concentration profiles of major, minor, and trace species were obtained for n-butane/DME/oxygen/argon at six different reactor inlet temperatures, and the results were compared with those attained for pure n-butane oxidation case (n-butane/oxygen/argon). Dimethyl ether addition decreased formations of various toxic species such as carbon monoxide, aromatic species, and polycyclic aromatic hydrocarbons, while it increased the formations of formaldehyde and acetaldehyde. Increasing equivalence ratio increased the formations of carbon monoxide, methane, aromatic species, and polycyclic aromatic hydrocarbons, while its effects on formaldehyde and acetaldehyde were not pronounced under the conditions studied. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Dimethyl ether; Oxygenated additives; n-Butane; Equivalence ratio; POLYCYCLIC AROMATIC-HYDROCARBONS; EMISSION CHARACTERISTICS; SOOT FORMATION; DME; FUEL; ENGINE; FLAMES; PERFORMANCE; COMBUSTION; KINETICS; Energy & Fuels; Engineering